ANALYSIS OF THE IMPACT OF E-SERVICE QUALITY, USER EXPERIENCE, AND SALES PROMOTION ON IMPULSIVE BUYING IN THE SOCO BY SOCIOLLA AND SEPHORA APPLICATIONS - Prayunita, Dinda Amira; Makky, Muhammad Al; Wibowo, Yanuar Firdaus Arie (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This study uses the PLS-SEM method to explore the effect of e-service quality, user experience, and sales promotion on impulse buying behavior on the SOCO by Sociolla and Sephora applications. The research is motivated by the competitive landscape of the e-commerce beauty and cosmetics sector, which demands an understanding of factors influencing impulsive buying. While previous studies emphasize e-service quality and user experience in customer satisfaction, their direct impact on impulsive buying remains unclear. Active users of the SOCO by Sociolla and Sephora applications provided information via an online questionnaire, which was then evaluated using SmartPLS. The findings demonstrate that sales promotions have a major and advantageous impact on impulsive purchasing, emphasizing the effectiveness of alluring offers like discounts, free shipping coupons, and special promotions for new users in inciting impulsive purchases. On the other hand, although crucial for overall satisfaction, e-service quality and user experience have no direct bearing on impulsive buying in this study. Current solutions focus on enhancing sales promotion strategies to attract more customers. However, further improvements in service quality and user experience could lead to higher customer loyalty and repeat purchases. Conclusively, the study offers significant perspectives to the e-commerce sector regarding the significance of inventive sales promotion tactics in stimulating spontaneous purchasing tendencies, underscoring the necessity of a well-rounded strategy that takes user experience and service quality into account.